PYRITE FROM HYDROTHERMAL ROCKS AS INDICATOR OF THE STRUCTURE OF A MODERN HIGH-TEMPERATURE HYDROTHERMAL SYSTEM: IMPLICATIONS FOR THE ORIGIN OF METALLIC MATTER - Rychagov S.N.; Sandimirova E.I.; Stepanov I.I. (My University, 1999)
Trace element composition and morphology of pyrite were analyzed in the metosomatic rocks of the modern Baransky (Iturup I.) and Pauzhetka (South Kamchatka) high-temperature hydrothermal systems. Pyrite occurs as disseminated particles in altered rocks and contains various metallic and nonmetallic elements: Au, Ag, As, Sb, Hg, Pb, Cu, Mn, Mo, V, Co, Ni, Zr, Li, Al, and others, the contents of which range between 0.00001 and 3.2%. This composition is consistent with the composition of modern endogenic hydrothermal solutions. The content of trace elements in pyrite from the cooling Pauzhetka system (solutions have temperatures below 220°C) is generally an order of magnitude higher than in the Baransky system which is in the state of progressive development (solutions in its interior are as hot as 350°C). The same trend holds in the Paratunka low-temperature (< 110°C) hydrothermal system from South Kamchatka, where the contents of the same trace elements in pyrite from metasomatic rocks are even higher. The zones of ascending and descending hot fluid flows differ in the trace element assemblages in pyrite. The contents of trace elements are drastically lower inside the thick liquid-vapor transition zones. The situation is different at the boundaries between them, where geochemical barriers facilitate the accumulation of Au, Ag, As, Sb, Hg, and other elements in pyrite and in the enclosing quartz-adular (quartz-adular-prehnite-wairakite-epidote) metasomatic rocks. Large zones of fluid boiling differ from the other hydrothermal structures by the pattern of their morphologically varying pyrite distribution. The possible sources of some metallic and nonmetallic components in the high-temperature hydrothermal systems are assumed to be a peripheral magmatic chamber inferred to be localized at a depth of > 2.0 km or an associated large cooling intrusive diorite body, whose top was exposed by boreholes and investigated by various methods.